2004
DOI: 10.1183/09031936.04.00097503
|View full text |Cite
|
Sign up to set email alerts
|

Normal nasal mucociliary clearance in CF children: evidence against a CFTR‐related defect

Abstract: Studies on mucociliary clearance (MCC) in cystic fibrosis (CF) have produced conflicting results. This study aimed to differentiate primary (ion transportrelated) from secondary (inflammatory) causes of delayed MCC in CF.Nasal MCC was measured in 50 children (CF, primary ciliary dyskinesia (PCD) and no respiratory disease). Nasal lavage fluid was analysed for interleukin (IL)-8 and tumour necrosis factor-a. Similar measurements were obtained in adult CF patients with and without chronic sinusitis (CS).Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…In advanced cystic fibrosis (CF), airways show goblet cell hyperplasia and submucosal gland hypertrophy, and imaging of radiolabeled particles deposited in the lung indicates that MCT is reduced (1,3). The MCT reduction is greater as the severity of the disease increases, consistent with the finding that reduced MCT has not been detected in young people with CF (15,16).…”
supporting
confidence: 74%
“…In advanced cystic fibrosis (CF), airways show goblet cell hyperplasia and submucosal gland hypertrophy, and imaging of radiolabeled particles deposited in the lung indicates that MCT is reduced (1,3). The MCT reduction is greater as the severity of the disease increases, consistent with the finding that reduced MCT has not been detected in young people with CF (15,16).…”
supporting
confidence: 74%
“…In addition, radioisotope studies show that people with CF are able to clear labelled particles from their distal airways and studies have demonstrated conserved mucociliary transport in CF [37,38,39]. Experiments on the in vitro tissue culture model may give some explanation to this paradox [40].…”
Section: Airway Physiologymentioning
confidence: 99%
“…Studies have shown that altered biophysical properties of mucus, and possibly MCC dysfunction itself, are secondary to infection in both CF and PCD lung disease (McShane et al, 2004;Grubb et al, 2004;Bush et al, 2006). Viscoelasticity has recently been shown to be an important factor in the formation of bacterial colonies (Matsui et al, 2006).…”
Section: Airway Surface Liquid Rheologymentioning
confidence: 99%